2015
DOI: 10.1093/ee/nvv001
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Soybean Insect Pollinators: Community Identification and Sampling Method Analysis

Abstract: Soybean, Glycine max (L.) Merrill, flowers can be a source of nectar and pollen for honey bees, Apis mellifera L. (Hymenoptera: Apidae), wild social and solitary bees (Hymenoptera: Apoidea), and flower-visiting flies (Diptera). Our objectives were to describe the pollinator community in soybean fields, determine which sampling method is most appropriate for characterizing their abundance and diversity, and gain insight into which pollinator taxa may contact soybean pollen. We compared modified pan traps (i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(76 citation statements)
references
References 37 publications
5
71
0
Order By: Relevance
“…Casual observation of soybeans during bloom indicated that honey bees did not visit soybean flowers, although we did identify a small amount of soybean pollen from two sites (no corn pollen was detected) and, further, honey bees and wild bees have been documented visiting soybeans (e.g. Erickson, 1975;Gill and O'Neal, 2015). As further evidence of drift, we detected chlorpyrifos most prevalently (50%, 80%, and 63% of pollen samples, respectively) at sites D, E and F; the three sites with the most non-forage (primarily corn and soybeans) surrounding them.…”
Section: Pesticide Exposurementioning
confidence: 68%
“…Casual observation of soybeans during bloom indicated that honey bees did not visit soybean flowers, although we did identify a small amount of soybean pollen from two sites (no corn pollen was detected) and, further, honey bees and wild bees have been documented visiting soybeans (e.g. Erickson, 1975;Gill and O'Neal, 2015). As further evidence of drift, we detected chlorpyrifos most prevalently (50%, 80%, and 63% of pollen samples, respectively) at sites D, E and F; the three sites with the most non-forage (primarily corn and soybeans) surrounding them.…”
Section: Pesticide Exposurementioning
confidence: 68%
“…Research investigating bee communities within non-pollinator dependent crops is rare; however recent studies in corn, soybean, biofuel crops (corn, switchgrass, mixed prairie species) [11,12,13,101,102], and now potato fields (this study) are improving understanding of bee diversity in non-pollinator dependent crops. Bee abundance and richness is typically lower in intensive crops relative to more diversified habitats [101], however a substantial number of bee species remain in these landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite agricultural landscape simplification, about 50–60 species of pollinators have been collected from soybean and corn monocultures, indicating that pollinators use and persist in these agroecosystems [11,12,13]. Potato fields produce temporary flushes of flowers that may attract species of polylectic native bees nesting in nearby undisturbed areas.…”
Section: Introductionmentioning
confidence: 99%
“…At the first four sites, bees were collected from abundantly blooming forbs by netting in a 30–60 minute period [34]. In the agricultural site, bees were collected in modified pan traps (i.e., bee bowls containing soapy water) [35]. The use of multiple field sites of different land use types across the season allowed for capture of a wide variety of bee species.…”
Section: Methodsmentioning
confidence: 99%